Fish Species Composition in the Dinh An Estuary, Tra Vinh Province - Huan, Nguyen Xuan; Duyen, Nguyen Thi; Nam, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The Dinh An estuary is one of two mouths of the Hau river and also one of the mouths of the Mekong river, which flows into the East Sea of Vietnam. It has characteristics of a delta estuary and is under the strong influence of the tide. Based on the specimens collected in three field surveys, conducted in July 2011, April 2012 and August 2015, we have identified 103 fish species belonging to 43 families and 13 orders in the Định An estuary. Among these fish orders, Perciformes made up the highest and far superior percentages at all taxonomic levels, with 19 families (accounted for 44.19% of total family number), 44 genera (accounted for 54.32% of total genus number), and 53 species (accounted for 51.46% of total species number). The other orders had much lower  number of species, genera, and families, with their percentages at each taxonomic level mostly lower than 10%. Even, there were six orders (46.15% of total order number) with only one family, one genus and one species in each. On average, each fish order found in the area was represented by 3.31 families, 6.23 genera and 7.92 species and each family was represented by 1.88 genera and 2.40 species. Among 103 fish species found in the area, 19 are pelagic and 84 are demersal, and one species, Otolithoidesbiauritus (Cantor, 1849) was listed at the Vulnerable level (VU) in Vietnam Red Data Book (2007). Results of this paper are the first published data of fish species composition in the Dinh An estuary. Keywords: Dinh An, estuary, fish species composition, identification, specimens.